2021
DOI: 10.1111/josi.12455
|View full text |Cite
|
Sign up to set email alerts
|

Beyond trauma: Decolonizing understandings of loss and healing in the Indian Residential School system of Canada

Abstract: Indigenous scholars and others who study the experiences of Indigenous communities have long criticized the psychocentric approach to trauma held by most clinical professionals. A recent example of this was the Canadian government's reparations for Indian Residential School system (IRS) survivors, which focused largely on individual psychological harms rather than broader effects of colonial oppression. Beginning in 1867 and continuing throughout the latter half of the twentieth century, Indigenous children we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…For example, would a similar pattern be found when the target groups were White and Indigenous faces? Given the recent discovery of hundreds of unmarked graves of Indigenous children who have died at residential schools in Canada (Burrage et al, 2021 ), examining another group that has also experienced extreme and systemic discrimination is important. Can perceived similarity increase attention to the eyes of White and Indigenous targets for White participants?…”
Section: Discussionmentioning
confidence: 99%
“…For example, would a similar pattern be found when the target groups were White and Indigenous faces? Given the recent discovery of hundreds of unmarked graves of Indigenous children who have died at residential schools in Canada (Burrage et al, 2021 ), examining another group that has also experienced extreme and systemic discrimination is important. Can perceived similarity increase attention to the eyes of White and Indigenous targets for White participants?…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have suggested that reclaiming loss as our epoch's shared denominator for human and non-human experiences may open pathways for identifying common tools to question colonial and corporate power (Adams, 2020). Losses resulting from imposed transformation, as in the present study, are likely experienced fundamentally differently from anxieties projected towards the future in Global North-settings (Adams, 2020; see also Burrage et al,2021). Yet, despite differences, sharing the terrifying feeling of loss may be among what can guide people and movements, such as the network that facilitated the present research, to explore ways of rememberment and coexistence in a breaking planet (Ndlovu-Gatsheni, 2020;Lynch & Veland, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…Participants felt strong ties to the mountains and responsibility for protecting the knowledge defended by earlier generations. The thought of losing these ties produced “future anxiety” (Sara) (Normann, 2021) and a sense of losing the collective self (Hogg & Williams, 2000) and the meaning of life (see also Burrage et al, 2021). In explaining the meaning of loss, Sara allowed a glimpse into her lifeworld:
It is a scary profession.
…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that in these cases, researchers did not want to bias the data in any given direction and instead asked neutral, open-ended questions to determine whether participants would spontaneously disclose data about culture. However, these articles stand in contrast to those where cultural data was specifically elicited (Betancourt et al, 2011; Burrage, 2018; Wexler, 2014) in relation to richness of description of cultural values.…”
Section: Discussionmentioning
confidence: 98%